Hysteroscopy in evaluation of intrauterine causes of AUB - Naik, Meena; Ratnani, Rekha; Thaore, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding is the most common gynecological problem comprising more than 30-50% of gynecological OPD patients. There are various causes of AUB from hormonal dysfunction to endometrial cancer. In order to manage effectively it is important to diagnose accurately the cause of abnormal bleeding. This study outlines the place of hysteroscopy and its role in evaluation of intrauterine causes of AUB. Methods: This is a Retrospective cross sectional observational study conducted in department of Obstetrics and Gynaecology at CCM Medical College, Durg, Chhattisgarh. 350 Patients between 20-70 years age presenting to general gynae OPD with abnormal uterine bleeding at CCM medical college over a period of 2 years between 1st January 2015 to December 2016 were studied. All patients were subjected to thorough clinical evaluation followed by sonography and hysteroscopy. Data collected from medical records, analysed and various intrauterine causes of AUB were studied. Results: Mean age of patients in our study was 45 years with majority of patients in 40-50 year age group. predominant complaint reported was menorrhagia (52%) followed by menometrorrhagia (18.86%) and polymenorrhoea (18.58%). USG detected abnormality in 65.6 % of cases and 34.4% were normal on USG but majority of these were fibroids and ovarian cysts. However, diagnosis of specific intrauterine pathology was made in only 12.8%. Hysteroscopy detected intrauterine abnormality in 60% cases. Most common being polyp in 94 patients (26.8%) followed by hyperplastic endometrium in 74 (21.1%). 18 (5.1%) patients had polypoidal endometrium which is also type of hyperplastic endometrium. 17 (4.85%) had submucous fibroid, 4 (1.1%) had atrophic lining and 3 (0 .85%) had intrauterine adhesions. Diagnostic accuracy of hysteroscopy was found better in polyps and submucous myomas which were missed by usg and also can be missed by traditional D and C only. Conclusions: Hysteroscopy allows exclusion of intracavitary pathology as well as treatment of them in same sitting with proper tissue biopsy from the abnormal area which can be of help in proper treatment planning. Though hysteroscopy helps in diagnosing cause of AUB their proper management will depend on final histology, age of patient and fertility goals.